Tetrasiklin HCL Gel 0,7% meningkatkan jumlah sel fbroblas dan mempertebal ligamen periodontal pada sulkus gingiva tikus yang mengalami periodontitis - I Gusti Agung Sri Pradnyani (DiscoverSys Inc., 2017)
Periodontal disease is an infectious disease, could be result loose of the teeth. This research is to prove that the applying 0.7% tetracycline hcl gel on rat gingival sulcus result higher number of fibroblasts and collagen synthesis which are marked by the thicker of rat periodontal ligament. The study was a randomized post test only control group design experimental study on 32 white male rats which are inducted by lipopolyssaccaride (LPS) for 8 days. And then rats divided into control group were given placebo, and treatment group were given 0.7% tetracycline HCL gel. On 10th days, the rats were euthanazided for taken mandibula alveolar bone tissue sampling and histological preparations were made by HE (Harris Hematoxylin-Eosin) staining. The data were analyzed using SPSS program processed using Shapiro Wilk for normality test and then continued using independent t-test. The result of this research is the mean number of fibroblasts at treatment group by administration of 0.7% tetracycline HCL gel (148.38±5.11 units) was higher than the control group (113.19±5.39 units). The mean of collagen synthesis was showed by the thickness of periodontal ligamen at group treated 0.7% tetracycline HCL gel (338.65±57.28 µm) was higher than the control group (225.50±45.29 µm). The mean number of fibroblast cell and thickness of periodontal ligament were statistically different (p<0.05). Thus, it is concluded that 0.7% tetracycline HCL gel enhance the number of fibroblasts cell and the thickness of periodontal ligament in rat with periodontal disease.